New conceptions about mourning for loss of the loved ones - Yoffe, Laura (2013)
In recent decades it has reached a reasonable agreement among researchers regarding concepts and manifestations associated with mourning (Stroebe et al., 2007). The progress are great from the conceptions of mourning “work” (Freud, 1917), the “phases” (Bowlby, 1980; Kubler Ross, 1984) and the “tasks” of mourning (Worden, 1991). A lot of recent research recognize the mourning as a complex phenomenon that includes biological, psychological, social and spiritual levels (Stroebe et al., 2007).New studies broadened and deepened the theory of stress confrontation present in negative and / or traumatic situations (Lazarus & Folkman, 1984) to investigate the cognitive, emotional, social and spiritual process that people of different ages use, belonging to different creeds and cultures to confront various types of losses (Stroebe et al., 2007; Folkman, 2007; Rosemblatt, 2007).One of the main findings of my doctoral thesis research performed with people of different creeds, is referred to the type of death and mourning as factors that influence the confront of the loss (Stroebe et al., 2011), as is the effect of the anticipation that prints the differences in the confront of mourning depending on the type of death, as anticipated or unexpected, sudden and / or tragic (Yoffe, 2012a).